Between Imagination and Innovation: The Role of Social Media in Craft Artists in South Sulawesi - Dyan Fauziah Suryadi; Muh. Indra Fauzi Ilyas; Harry Yulianto; Iryani Iryani (AIBPM Publisher, 2025)
This study examines the dualism of creativity and innovation among craft industry players in South Sulawesi, focusing on the tension between traditional imagination and the influence of social media. In the digital era, the local craft industry faces the challenge of maintaining authenticity while meeting modern market demands. The research analyzes how these two approaches shape creative processes, product innovation, and business strategies. Using a qualitative methodology with in-depth interviews, two groups of craft players were identified: traditionalists, who rely on imagination and reject digital influences, and digitalists, who actively use social media for inspiration and business development. The findings reveal that traditionalists emphasize authenticity and artistic integrity, with innovation occurring incrementally. In contrast, digitalists integrate tradition with global trends, using social media as a tool for market-oriented innovation and business sustainability. These results contribute theoretically by enriching the literature on creativity dualism in the creative industry and offer practical implications for craft practitioners. The study suggests the adoption of hybrid strategies that combine the strengths of tradition with digital opportunities. Future research is recommended to explore business models that successfully navigate this dualism and ensure both cultural preservation and market competitiveness.